Interplay between the Zur Regulon Components and Metal Resistance in Cupriavidus metallidurans - Bütof, Lucy (J Bacteriol, 2019)
The Zur regulon is central to zinc homeostasis in the zinc-resistant bacterium Cupriavidus metallidurans. It comprises the transcription regulator Zur, the zinc importer ZupT, and three members of the COG0523 family of metal-chaperoning G3E-type GTPases, annotated as CobW1, CobW2, and CobW3. The operon structures of the zur and cobW1 loci were determined. To analyze the interplay between the Zur regulon components and metal resistance, deletion mutants were constructed from the wild-type strain CH34 and various other strains. The Zur regulon components interacted with the plasmid-encoded and chromosomally encoded metal resistance factors to acquire metals from complexes of EDTA and for homeostasis of and resistance to zinc, nickel, cobalt, and cadmium. The three G3E-type GTPases were characterized in more detail. CobW1 bound only 1 Zn atom per mol of protein with a stability constant slightly above that of 2-carboxy-2′-hydroxy-5′-sulfoformazylbenzene (Zincon) and an additional 0.5 Zn with low affinity. The CobW1 system was necessary to obtain metals from EDTA complexes. The GTPase CobW2 is a zinc storage compound and bound 0.5 to 1.5 Zn atoms tightly and up to 6 more with lower affinity. The presence of MgGTP unfolded the protein partially. CobW3 had no GTPase activity and equilibrated metal import by ZupT with that of the other metal transport systems. It sequestered 8 Zn atoms per mol with decreasing affinity. The three CobWs bound to the metal-dependent protein FolE(IB2), which is encoded directly downstream of cobW1. This demonstrated an important contribution of the Zur regulon components to metal homeostasis in C. metallidurans. IMPORTANCE Zinc is an important transition metal cation and is present as an essential component in many enzymes, such as RNA polymerase. As with other transition metals, zinc is also toxic at higher concentrations so that living cells have to maintain strict control of their zinc homeostasis. Members of the COG0523 family of metal-chaperoning GE3-type GTPases exist in archaea, bacteria, and eucaryotes, including humans, and they may be involved in delivery of zinc to thousands of different proteins. We used a combination of molecular, physiological, and biochemical methods to demonstrate the important but diverse functions of COG0523 proteins in C. metallidurans, which are produced as part of the Zur-controlled zinc starvation response in this bacterium.